Introducing a Process-Oriented Framework for the Design of Advertising Campaigns - Maysam Shafiee; Parasto Iranpak; Mohammad Zand (Journal of Digital Information Management, 2024)
Research on advertising campaigns is intriguing due to their recent emergence and rapid expansion. These campaigns encounter various challenges, such as determining the most effective advertising strategies to achieve their objectives. This study aims to present a practical model for advertising campaigns, outlining the necessary steps for companies to follow. The research methodology involved a qualitative analysis of 180 advertising-related articles, with 80 articles selected as a sample through library studies. Data collection included semi-structured interviews with 10 advertising experts and the distribution of an open questionnaire to identify key indicators. The findings led to developing a framework comprising 9 categories, 27 themes, and 54 indicators for advertising campaigns. Indicators such as storyboards, client briefs, campaign scripting, and slogan writing are identified as novel elements within campaign models, offering valuable insights for advertising organizations.

Empirical Analysis on the Efficiency of Clustering Algorithms Based on the Significance of Cluster Size - Sunitha Cheriyan; Shaniba Ibrahim; Susan Treesa (Journal of Digital Information Management, 2023)

ERP Project Lifecycle costs: A Review- - L’YARFI Hanane; MOTAKI Noureddine; DERRHI Mostafa; LAHLOU Imane (Journal of Digital Information Management, 2023)
Today, many organizations acquire and implement enterprise resource planning (ERP) solutions to improve their operations performance and create value. However, they fail to achieve these objectives due to a lack of knowledge and a better estimating of all the costs related to an ERP system project. The purchasing costs of ERP systems are the most visible expense for many organizations that have adopted ERP systems, but the entire ERP lifecycle phase of implementation contains many hidden costs. As a result, institutions have long struggled with information system implementation cost overruns. This document presents the research on the various costs associated with the different stages of the life cycle of the REP project according to the literature on ERP lifecycle costs.

Incorporating Quality Measurement into Scientific Document Retrieval – - Nedra Ibrahim; Anja Habacha Chaibi; Henda Ben Ghézala (Journal of Digital Information Management, 2021)
One of the challenges facing today's researchers is how to find qualitative information that meets their needs. In scientific research, the quality of information is very important for institution quality improvement and research validation. The main purpose of the paper is the proposal of a scientometric annotation approach to improve retrieval system performance and meet researchers’ needs. In this work, we discuss how to use scientometrics in document annotation to improve information quality. One possible solution to this problem is to automate and facilitate the selection of qualitative scientific documents by enriching the document annotation process with scientometric criterion. Our approach provided better performance for retrieval system compared to BM25 retrieval model. The best performance was supplied by the integration of document citation number and journal or conference ranking. The best improvement rate was 34.21% in F-measure, 52.22% in nDCG, 27.45% in MAP and 83.33% in P(k). An important implication of this finding is the existence of correlation between research paper quality and paper relevance.

Is the Binary Search Faster when Two Variables are Added in the Middle of the Data?- - Djasen Tjendry; Wirawan Istiono (Journal of Digital Information Management, 2020)
Modern architecture has developed new algorithms for large and distributed data, In this digital era, algorithms which intended to quickly process, search, and sort data are very much needed by IT developers. This research will discuss the modification of Binary Search Algorithm, which is previously known for its existing low, mid, and high variables. This research will discuss how we can modify the binary search algorithm by adding two variables- the variable mid-low and mid-high. It will show how by adding two variables between the mid variable could improve the performance of the Binary Search Algorithm.

Investigating the Determinant and Impact of Digital Library Engagement: A Conceptual Framework – - Mohamad Rahimi Mohamad Rosman; Mohd Nasir Ismail; Mohamad Noorman Masrek (Journal of Digital Information Management, 2019)
Facing an unprecedented explosion and growth of Information and Communication Technology (ICT) signal the overwhelming dependency on the digital library (DL). Over the years, libraries spent a great amount of investment to subscribe to various digital resources such as online databases, electronic journals, electronic books and other digital resources. However, previous studies reported that the use of DL is underutilized; hence undermining its original purposes and making it harder for the libraries to justify their investment on DL resources. It is reported that users prefer to use free online resources compared to the DL resources. The lack of DL usage is credited to the lack of DL engagement and the impact of contextual factors leading to DL engagement. Yet, not much is known about the contributing factors of DL engagement as well as its impacts. Therefore, the purpose of this paper is twofold: (1) to introduce the concept of Digital Library Engagement, and (2) to discuss at the conceptual level on the determinants and impacts of digital library engagement and development of a conceptual framework. In order to develop the conceptual framework, the study adopted a systematic literature review approach of over 100 papers. Grounded in previous literature on DL, the contributions of this paper are as follows: first, the paper provides insight on the new concept of digital library engagement; second, the paper proposes

Investigating the Determinant and Impact of Digital Library Engagement: A Conceptual Framework - Mohamad Rahimi Mohamad Rosman; Mohd Nasir Ismail; Mohamad Noorman Masrek (Journal of Digital Information Management, 2019)

Identification of Sunspots on SODISM Full-Disk Solar Images - Amro F. Alasta; Abdulrazag Algamudi; RamiQahwaji; Stan Ipson (Journal of Multimedia Processing and Technologies, 2018)

Model of “International Megalesson” of Learning Programming in Schools of Russia and Kazakhstan - Zhamilya Akkassynova; Nikolay Pak; Liubov Ivkina (Progress in Computing Applications, 2018)

Feasibility of digital forensic examination and analysis of a cloud based storage snapshot - Almulla, S.; Iraqi, Y.; Jones, A. (Journal of Digital Information Management, 2017)

High level mammographic information fusion for real world ontology population - Salem, Y.B.; Idodi, R.; Ettabaa, K.S.; Hamrouni, K.; Solaiman, B. (Journal of Digital Information Management, 2017)

Investigating factors influencing non-use and abandonment of microblogging services - Guo, Y.; Goh, D.H.-L.; Ilangovan, K.; Jiao, S.; Yang, X. (Journal of Digital Information Management, 2012)
This study explores the reason for non-usage and abandonment of microblogging. While previous studies mainly focused on individual behaviors associated with the use of social media, this research identifies why people do not use, or terminate their microblogging accounts. Studying the reasons for non-usage and abandonment is important as it helps organizations devise strategies to counteract this behavior by addressing nonusers' concerns. First, focus group interviews were conducted to uncover non-usage reasons. The elicited reasons were then used to construct a survey instrument and administered. Our results suggests that preference for other technologies, privacy concern and time constraints are the top three reasons contributing to the non-use and abandonment of microblogging accounts. The paper also proposes potential improvements to microblogs to attract more users.
Keywords: Abandonment; Focus Group; Microblogging; Non-use; Social media; Social networks; Survey

Password based anonymous authentication with private information retrieval - Nakamura, T.; Inenaga, S.; Ikeda, D.; Baba, K.; Yasuura, H. (Journal of Digital Information Management, 2011)
This paper focuses on authentication with three types of entities: a user who sends an authentication request, a service provider who receives and verifies the request, and a database who supplies the service provider with information for verifying the request. This paper presents novel authentication protocols that satisfy the following important properties: (1) secure against replay attacks and (2) the database cannot identify which user is authenticating. First, we show a protocol which satisfies Properties (2). Second, we show a protocol which satisfies Properties (1) and (2). A key idea of our authentication protocols is to use private information retrieval (PIR) [Chor et al. J. ACM, 1998].
Keywords: Anonymity; Authentication; Privacy protection; Private information retrieval

A refined methodology for automatic keyphrase assignment to digital documents - Khan, S.; Fatima, I.; Irfan, R.; Latif, K. (Journal of Digital Information Management, 2011)
Keyphrases precisely express the primary topics and themes of documents and are valuable for cataloging and classification. Manually assigning keyphrases to existing documents is a tedious task; therefore, automatic keyphrase generation has been extensively used to classify digital documents. Existing automatic keyphrase generation algorithms are limited in assigning semantically relevant keyphrases to documents. In this paper we have proposed a methodology to refine the result set of automatically generated keyphrases by Keyphrase Extraction Algorithm (KEA++), so that the keyphrases accurately and precisely represent the content of the document. Our approach is an additional layer at the top of KEA++ and exploits semantic relationships and hierarchical structure of the controlled vocabulary to filter out irrelevant keyphrases from the result set generated by KEA++. The methodology was applied on different sets of academic publications for evaluation. Evaluation demonstrates that the proposed refinement methodology improves the quality of generated keyphrases.
Keywords: Automatic indexing; Keyphrase assignment; Vocabulary

An approach for matching schemas of heterogeneous relational databases - Karasneh, Y.; Ibrahim, H.; Othman, M.; Yaakob, R. (Journal of Digital Information Management, 2010)
Schema matching is a basic problem in many database application domains, such as data integration. The problem of schema matching can be formulated as follows, "given two schemas, Si and Sj, find the most plausible correspondences between the elements of Si and S j, exploiting all available information, such as the schemas, instance data, and auxiliary sources" [24]. Given the rapidly increasing number of data sources to integrate and due to database heterogeneities, manually identifying schema matches is a tedious, time consuming, error-prone, and therefore expensive process. As systems become able to handle more complex databases and applications, their schemas become large, further increasing the number of matches to be performed. Thus, automating this process, which attempts to achieve faster and less labor-intensive, has been one of the main tasks in data integration. However, it is not possible to determine fully automatically the different correspondences between schemas, primarily because of the differing and often not explicated or documented semantics of the schemas. Several solutions in solving the issues of schema matching have been proposed. Nevertheless, these solutions are still limited, as they do not explore most of the available information related to schemas and thus affect the result of integration. This paper presents an approach for matching schemas of heterogeneous relational databases that utilizes most of the information related to schemas, which indirectly explores the implicit semantics of the schemas, that further improves the results of the integration.
Keywords: Biomedical database; Database integration; Heterogeneous; Schema matching

Extraction of characteristic description for analyzing news agencies - Ishida, S.; Ma, Q.; Yoshikawa, M. (Journal of Digital Information Management, 2010)
News agencies report news from different viewpoints and with different writing styles and these differences often ap pear in their article descriptions. We propose a method to extract characteristic descriptions on certain entities (persons, locations, organizations, etc.) in news agency articles. For a given entity, a description is one tuple (called an SVO tuple) consisting of that entity and other words or phrases appearing in the same sentence on the basis of their SVO (Subject (S), Verb (V) and Object (O)) roles. We extract characteristic descriptions of entities by computing the fre quency and inverse agency frequency of each description. By arranging characteristic descriptions chronologically, we were able to ascertain the left-or right-leanings of news agencies and how those leanings varied with the passage of time.
Keywords: News agencies; News analysis; Text characteristics; Text description; Word frequency analysis

Multi-objective optimization in service systems - Gonsalves, T.; Yamagishi, K.; Itoh, K. (Journal of Digital Information Management, 2010)
Muti-objective optimization deals with the simultaneous optimization of two or more conficting objective functions in real-life systems. This paper deals with the multi-objective optimization in service systems. The goal of service systems is to provide cost-efficient service to customers, while at the same time, reducing the customer waiting time for service. In general, a low cost in system operation leads to longer waiting times, while a higher cost in system operation leads to shorter waiting times. The two objectives - service cost (operational cost) and waiting time (customer satisfaction) are, therefore, conficting in nature. We use the novel Multi-Objective Particle Swarm Optimization (MOPSO) algorithm to optimize the two conficting objective functions simultaneously. MOPSO is a fairly recent swarm intelligence meta-heuristic algorithm known for its simplicity in programming and its rapid convergence. The multi-objective optimization procedure is illustrated with the example of a practical service system. MOPSO produces a family of well-spread Pareto fronts for the two objective functions in the practical service system.
Keywords: Multi-Objective Particle Swarm Optimization; Service cost; Service systems; Simulation optimization

Spam blog filtering with bipartite graph clustering and mutual detection between spam blogs and words - Ishida, K. (Journal of Digital Information Management, 2010)
This paper proposes a mutual detection mechanism between spam blogs and words with bipartite graph clustering for filtering spam blogs from updated blog data. Spam blogs are problematic in extracting useful marketing information from the blogosphere; they often appear to be rich sources of information based on individual opinion and social reputation. One characteristic of spam blogs is copied-and-pasted articles based on normal blogs and news articles. Another is multiple postings of the same article to increase the chances of exposure and income from advertising. Because of these characteristics, spam blogs share common words, and such blogs and words can form large spam bi-clusters. This paper explains how to detect spam blogs and spam words with mutual filtering based on such clusters. It reports that the maximum precision, or F-measure, of the filtering is 95%, based on a preliminary experiment with approximately six months' updated blog data and a more detailed experiment with one day's data. An advantage of this method for spam blog filtering, as compared to a machine learning approach, is also supported by experiments with SVM.
Cited By (since 1996):1Export Date: 10 July 2014
Keywords: Bipartite graph; Clustering; Filtering; Mutual detection; Spam blog; Spam word

Web Architectural-Inducing Model (WA-IM) for Information Architecture in cultural context: An empirical investigation - Mohd Isa, W.A.R.W.; Md Noor, N.L.; Mehad, S. (Journal of Digital Information Management, 2010)
Website Information Architecture (IA) is primarily treated as a new discipline that is concerned with design principles and architecture of information in digital landscape. Proliferation of revolutionary models for interdisciplinary applications of IA, however lack theoretical perspectives, empirical evidence and cultural context. Here, we proposed a new model called Web Architectural-Inducing Model (WA-IM). The model was developed based from existing literature and available architectural proposition from prior work. We tested the model suggesting that website IA being conceptualized as multidimensional constructs by exploring the applicability of WA-IM to web localization process from a socio-cognitive cultural perspective. The research methodology involves a web-based survey on Muslim online user as the cultural case study where 427 usable international responses were accumulated. The construct validation of the multifactor structure of website IA was assessed via confirmatory factor analysis (CFA) by using structural equation modeling. AMOS 7.0 was used to evaluate the five factor hypothesis goodness fit model. The result revealed that website IA is indeed a multidimensional construct composed of five factors: content-information, content-trust, navigation-traits, navigation-wayfindings and context. We conclude our study by providing empirical evidence for WA-IM in a form of goodness-fit-structure as part of the localization process towards the creation of cultural information structure.
Keywords: Human computer interaction; Information architecture; Information structure; Website information architecture

A Web-based surveillance system for traffic behavior and its application for practical recommendation of crosswalk installation - Imai, Y.; Hori, Y.; Masuda, S. (Journal of Digital Information Management, 2010)
A Web-based surveillance system has been developed to observe some intrusion into dangerous and security area. It is designed based on a Linux PC with Web services, Open CV engine, remote monitoring camera, remote controlling sub-server and other facilities. It supports users of mobile phones. Its image understanding facility by Open CV engine gives us information about intruders' tracks at the monitored places. As the result, it is beneficial that we can exactly know moving direction of intruders. Traffic security is one of the most important problems to be improved for our daily environment. In order to monitor traffic behavior, the surveillance system has been customized and applied to monitor traffic behavior about a specific area. It can acquire data about intruders' tracks when they go across relatively narrow streets. Such data provide information about suitable place to realize a necessary crosswalk which will comply with silent but real intruder's requests. Its monitoring function and image processing one are not so excellent but there are significant results for surveillance by means of limited adoption and adjustment. And we can recommend installation of Crosswalk based on intruders' tracks with image processing function of the surveillance system. It is concluded that our surveillance system is efficient enough to observe a specific place, compute image understanding about it and mine some kind of useful information of intruder's periodical behaviors.
Keywords: Evidence-based recommendation; Image understanding; Mobile computing; Surveillance system

Cache Pre-fetching and Replacement strategies for location dependent data in mobile environments - Mary Magdalene Jane, F.; Ilayaraja, N.; Nadarajan, R. (Journal of Digital Information Management, 2009)
In this paper, new strategies for prefetching and cache replacement are proposed. The proposed pre-fetching algorithm considers the geographical and semantic adjacency between queried items. The strategy is to pre-fetch the most probable secondary service as a by-product of the execution of a query to a primary service. Association rule mining is used for determining the secondary item that should be pre-fetched. The latter part of the paper deals with a cache replacement algorithm PAID+ (Probability Area Inverse Distance +) which takes into account the access probability and distance between the mobile client and the service item which suits a pre-fetching environment. The experimental evaluations using synthetic datasets show the cache pre-fetch and replacement policy PAID+ are effective in improving the system performance in terms of the cache hit ratio of mobile clients.
Keywords: Cache replacement; Location dependent data; Prefetching algorithm

Machine learning based work task classification - Granitzer, M.; Rath, A.S.; Kröll, M.; Seifert, C.; Ipsmiller, D.; Devaurs, D.; Weber, N.; Lindstaedt, S. (Journal of Digital Information Management, 2009)
Increasing the productivity of a knowledge worker via intelligent applications requires the identification of a user's current work task, i.e. the current work context a user resides in. In this work we present and evaluate machine learning based work task detection methods. By viewing a work task as sequence of digital interaction patterns of mouse clicks and key strokes, we present (i) a methodology for recording those user interactions and (ii) an in-depth analysis of supervised classification models for classifying work tasks in two different scenarios: a task centric scenario and a user centric scenario. We analyze different supervised classification models, feature types and feature selection methods on a laboratory as well as a real world data set. Results show satisfiable accuracy and high user acceptance by using relatively simple types of features.
Cited By (since 1996):6Export Date: 10 July 2014
Keywords: Data model; Data structure; Work task classification user interaction

Students' review of acceptance, usability and usefulness of WebLab-Deusto - García-Zubia, J.; Orduña, P.; Hernández, U.; Angulo, I.; Irurzun, J. (Journal of Digital Information Management, 2009)
The paper shows the results of the evaluation of three remote labs implemented at the University of Deusto -WebLab-Deusto- as a learning tool. The paper presents the results of the surveys done by students since 2004. This survey consists of some questions and its main objective is to measure the acceptance, usability and usefulness of the remote laboratory developed at University of Deusto. To the best of our knowledge, this survey is the largest one in terms of number of academic years and total number of students involved.
Cited By (since 1996):1Export Date: 10 July 2014
Keywords: Computing architecture; Hardware; Remote laboratories; Web laboratories

Model-driven development of content-based image retrieval systems - Ignatova, T.; Heuer, A. (Journal of Digital Information Management, 2008)
Generic systems for content-based image retrieval (CBIR), such as QBIC [7] cannot be used to solve domain-specific image retrieval problems, as for example, the identification of manuscript writers based on the visual characteristics of their handwriting. Domain-specific CBIR systems currently have to be implemented bottom up, i.e. almost from scratch, each time a new domain-specific solution is sought. Inspired by the recognition, that CBIR systems, although developed for different domain-problems, comprise similar-building blocks and architecture, the idea of adopting model-driven development techniques for generating CBIR systems was elaborated. To support the design of domain-specific CBIR-Systems on a conceptual level by reusing data structure and functional interfaces a framework model is developed, which can be used to derive concrete domain-specific CBIR models. A transformation approach for the generation of a platform-specific implementation on top of an object-relational database from the concrete conceptual model is proposed. Finally, how these techniques can be applied for the design of a CBIR system for the identification of music manuscript writers based on the visual characteristics of their handwriting is demonstrated.
Cited By (since 1996):1Export Date: 10 July 2014
Keywords: Content-based image retrieval; Model-driven development

Multiple description coding of an audio stream by optimum recovery transforms - Ito, A.; Makino, S. (Journal of Digital Information Management, 2008)
In this paper, we discuss a method of splitting one audio stream into two equal-quality streams and recover the original audio stream from only one of the split streams. From a mathematical consideration, it is found that the sum of errors of two recovered signals is equal to the power of the original signal if simple recovery is carried out. Next, we describe the optimum recovery transform. This method utilizes the covariance matrix of the signal to minimize the error of the recovered signal. We carried out several experiments to recover a signal from one of the split signals. The result showed that the optimum recovery transform gave better results than the simple recovery, while the best splitting transform differed according to the signal to be processed.
Cited By (since 1996):1Export Date: 10 July 2014
Keywords: Audio coding; Audio signal; Multiple description coding; Optimum recovery transform

Route navigation method for disabled access GIS in consideration of abilities and psychologies - Izumi, S.; Kobayashi, G.; Yoshida, T. (Journal of Digital Information Management, 2008)
This paper aims to propose a route navigation method for disabled access GIS. We focused the disabled's psychologies as well as their physical conditions. This paper represents quantization of physical and psychological burden of the disabled persons inflicted by various barrier factors. Also it represents estimation of total burden of a route to determine the optimum route. The route is represent ed by graph theory and route navigation method which is based on Dijkstra algorithm is applied. We extend the algorithm to make it possible to provide information on obstacles even when there are no accessible routes available to destination. The result of this study is being implemented and published as 3D Web Disabled Access GIS.
Cited By (since 1996):1Export Date: 10 July 2014
Keywords: Dijkstra algorithm; Disabled GIS access; Route navigation

Contextualizing multimedia semantics towards personalised eLearning - Eze, E.; Ishaya, T.; Wood, D.M. (Journal of Digital Information Management, 2007)
Recent developments of the Internet and the World Wide Web (WWW) have resulted in the proliferation of multi-media, resources and learning with existing multimedia web resources on the Web is becoming more prevalent and important. While recent standardization efforts in eLearning such as LOM, SCORM, and IMS Learning Design work towards learning content description, packaging, and delivery; existing eLearning solutions still lack the ability to adequately use multi-media resources to provide a learner with personalised learning resources. Effective use of multimedia for web-based learning provides quality interactive learning experience, but current techniques does not adequately provide a semantic approach for organising multimedia resources. With evolving trend in learning through the use of web technology, eLearning systems are expected to provide personalised learning resources for effective learning. We have accordingly proposed a way of organising existing multimedia resources based on contexts towards providing a truly personalised eLearning experience. This paper presents a framework for achieving context-based multimedia semantic annotation and organisation towards personalised learning.
Keywords: Multimedia technology; Web based learning; WWW

A multilingual query processing system using software agents - Idicula, S.M.; David Peter, S. (Journal of Digital Information Management, 2007)
The goal of this work was developing a query processing system using software agents. Open Agent Architecture framework is used for system development. The system supports queries in both Hindi and Malayalam; two prominent regional languages of India. Natural language processing techniques are used for meaning extraction from the plain quety and information from database is given back to the user in his native language. The system architecture is designed in a structured way that it can be adapted to other regional languages of India. This system can be effectively used in application areas like e-governance, agriculture, rural health, education, nabonal resource planning, disaster management, information kiosks etc where people from all walks of life are involved.
Keywords: Database design; Interfaces; Query processing; Software agents